Effects of Cultural Practices on Cold Protection: HS119/CH005, 5/2020 - Futch, Stephen H. (EDIS, 2020)
The relation of cultural practices to freeze damage will refer to radiation freezes (windy conditions) unless otherwise stated. Advective freezes, such as those that occurred in the 1980s, behave differently. Most of the principles in this documente apply for all freezes but are less effective during windy freezes because of the rapid air movement and transport of cold air during these events. First published in June 1992.